GENRE SPECIFICITY AND SOCIO-CULTURAL CONNOTATIONS OF MODERN UKRAINIAN ETHNO-FANTASY (BASED ON V. KLYMCHUK’S NOVEL “RUTHENIA. THE WITCH’S RETURN”) - Deviatko, Nataliia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
This article offers a literary analysis of Vitaliy Klymchuk’s novel Ruthenia: The Witch’s Return, examined as a representative example of contemporary intellectual ethno-fantasy. The relevance of the study is обусловлена the transformation of fantasy from a predominantly entertainment-oriented genre into a philosophically charged narrative that draws on authentic mytho-folkloric material to reflect present-day challenges, particularly those shaped by the Russian–Ukrainian war. Special attention is given to the novel’s linguopoetics. The study demonstrates that the use of synesthetic imagery, the anthropomorphization of natural forces, and rhythmic prose functions as a means of externalizing the characters’ inner states. The author’s model of the fictional world is grounded in an implicit correlation between the psychotypes of the characters and the mental and cultural patterns of contemporary Ukrainian society. Through the conceptual lenses of ressentiment and postcolonial trauma, the article examines mechanisms of social degradation, ranging from latent moral erosion to fully developed forms of totalitarian degeneration. The concept of “conquest without war” is articulated through strategies of consciousness manipulation and the normalization of “diffuse evil,” which penetrates society through individual moral compromises. The article further explores the novel’s ethical paradigm, focusing on the conflict between utilitarian logic and the deontological ethics consistently upheld by the protagonist. An internal ethical tension within the image of Ruthenia is identified, arising from the contradiction between an absolute humanistic ideal and enforced passivity in the face of tragedy. An analysis of the demiurgic figures Dobrovin and Akhruman reveals the problem of ethical asymmetry and the relativity of the categories of good and evil within the narrative. The conclusions emphasize the limited transformative potential of the model of resistance presented in the novel: despite the protagonists’ victory in a private confrontation, no systemic social change occurs, underscoring the cyclical nature of evil. The novel is interpreted as an unsettling warning that encourages reflection on issues of national agency and individual responsibility for the ethical foundations of the community. The study also substantiates the novel’s orientation toward an adult readership and its significance for the development of contemporary Ukrainian fantasy discourse.